Crystallization, recrystallization, and melting of polymer crystals on heating and cooling examined with fast scanning calorimetry. Issue 2 (7th August 2018) - Furushima, Yoshitomo; Schick, Christoph; Toda, Akihiko
Abstract: Fast scanning calorimetry (FSC) has been used to investigate the kinetics of nonisothermal crystallization, isothermal crystallization, and melting for semicrystalline polymers (ie, poly(butylene terephthalate, polyphenylene sulfide, and isotactic polypropylene). The scanning rate dependence of enthalpy of melt‐crystallization, cold‐crystallization, and recrystallization obtained from FSC are quantitatively explained on the basis of Ozawa's method. For isothermal kinetics, FSC allows to obtain the annealing‐temperature dependence of crystallization half‐time in a wide range of the supercooling without any unwanted nucleation or crystallization during cooling. The effect of additives for nonisothermal or isothermal crystallization was also considered in this article. In addition, hyphenated technique of FSC and polarized optical microscopy clearly shows the differences in crystallization kinetics and morphologies. Abstract : Fast scanning calorimetry (FSC) has been used to investigate the kinetics of nonisothermal crystallization, isothermal crystallization, and melting for semicrystalline polymers (ie, poly(butylene terephthalate, polyphenylene sulfide, and isotactic polypropylene). The scanning rate dependence of enthalpy of melt‐crystallization, cold‐crystallization, and recrystallization obtained from FSC are quantitatively explained. The effect of additives for the crystallization kinetics was also considered in this article. Hyphenated technique of FSC and polarized optical microscopy clearly shows the differences in crystallization kinetics and morphologies.